(untitled) (Pulse, 2025)
This report describes two successful cases of lateral tongue squamous cell carcinoma (SCC) reconstructed using a submental island flap following surgical resection. Case 1: A 59-year-old woman, presented with a 3.1 × 5.4 cm lesion on the left lateral tongue. She underwent wide local excision with supraomohyoid neck dissection, followed by reconstruction using a 7 × 4 cm pedicled submental island flap comprising skin, subcutaneous tissue, platysma, anterior belly of the digastric, and part of the mylohyoid muscle. Postoperative recovery was uneventful. At six months, she had regained oral intake and speech. Two-year follow-up confirmed excellent functional and aesthetic outcomes with no donor-site morbidity. Case 2: A 45-year-old man with grade II squamous cell carcinoma of the left lateral tongue (1.5 × 1.8 cm, depth of invasion 10 mm), underwent wide local excision with supraomohyoid neck dissection. A submental island flap was used for reconstruction. Recovery was smooth, with restoration of oral function by the second postoperative week. Beard growth over the flap was managed successfully with laser depilation. At one-year follow-up, healing was complete with satisfactory functional outcome. These cases highlight the submental island flap as a reliable, well-vascularized, functionally effective, and cosmetically acceptable option for tongue reconstruction after oncologic resection. It offers a resource-efficient alternative to free microvascular flaps, avoiding the need for microsurgical anastomosis and minimizing donor site morbidity. Pulse Vol.17, 2025 P: 48-52